Las Estrategias Metodológicas Y Su Incidencia En La Calidad Del Aprendizaje Estudiantil En El Área De Ciencias Sociales De La Escuela De Educación Básica “León De Febres Cordero”, Parroquia San Juan, Cantón Puebloviejo, Provincia Los Ríos. - Vera Aguirre, Digna María (2015)
The quality of education is all a number of processes that allow the student to optimally absorb knowledge and apply them in daily life. The methodological strategies are part of the process of teaching and learning, and if not properly applied in the classroom, antlers strategies would be failing in its functionality and yet not allow the development of critical thinking in students and there would be quality in learning. This research topic is themed "The methodological strategies and their impact on the quality of student learning in the area of social sciences at the School of Basic Education" León Febres Cordero "parish San Juan Pueblo Viejo Canton, Los Ríos province "in which it was determined through the use of surveys and observation, that teachers are not applying methodological strategies to the quality of learning; because the quality of learning depends largely on the work of the teacher in the planning and running in the classroom through the methodological strategies to achieve the significance of the contents that students receive. It was concluded that teachers School of Basic Education "León Febres Cordero" parish San Juan Pueblo Viejo Canton province Rivers, is not applying methodological strategies to the quality of learning and which are using no They meet the functionality for which they are designed and how a proposed teacher training was raised.